INTERNATIONAL COOPERATION AND THE DEVELOPMENT DEBATE: THE SHORTCOMINGS OF THEORY VERSUS THE ALLURE OF AGENDAS - Koldo Unceta Satrustegui; Jorge Gutiérrez-Goiria (Revista de Economía Mundial, 2018)
Development Cooperation, in addition to clear social and political support, originated from a context which represented a coherent contribution within the framework of Development Theory. However, from the 1980s with the rise of neoliberal ideas, debates on development and the international cooperation system and its strategies took different directions. Currently, the definition and monitoring of the Agenda has become the centre of debate, with the consequent abandonment of the theoretical and historical perspectives as well as the traditional perception of development as a process of transformation of reality. This disconnection between ideas on development and cooperation has led to a long-standing confusion over cooperation, with its role becoming increasingly unclear. This paper highlights the need to return to the relationship between theoretical reflection on development and cooperation strategies, through a process of identifying problems, studying their causes and consequently designing strategies. The way in which these links are created will open up the possibility of proposing alternatives according to the risks and challenges to be faced.